Pengaruh Brand Ambassador “Blackpink” Terhadap Repurchase Intention Produk Oreo X Blackpink Melalui Brand Image Sebagai Variabel Intervening: Studi pada Konsumen Oreo X Blackpink di Surabaya - Erin Dwi Cahyani; Jojok Dwiridotjahjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Brand Ambassadors on Repurchase Intention through Brand Image as an intervening variable. The population used consists of all consumers who purchase Oreo X Blackpink products. The sample size is 100 respondents. Data collection was carried out by distributing questionnaires through Google Form using non-probability sampling technique with purposive sampling method. The data analysis techniques used include validity testing, reliability testing, classical assumption testing (normality test, multicollinearity test, and heteroscedasticity test), hypothesis testing (t-test and coefficient of determination), and path analysis using SPSS version 26 as the testing tool. The results of this study indicate that the Brand Ambassador variable significantly influences Brand Image. The Brand Ambassador variable also significantly influences Repurchase Intention. The Brand Image variable significantly affects Repurchase Intention. Furthermore, the Brand Ambassador variable significantly influences Repurchase Intention through Brand Image as an intervening variable.